2011
DOI: 10.1016/j.acvd.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in women with heart disease in sub-Saharan Africa

Abstract: Heart disease severely impacts maternal and foetal outcome in our study. Pregnant women who underwent appropriate valve replacement before pregnancy had a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 10 publications
6
83
3
1
Order By: Relevance
“…Prosthetic valve patients tolerated pregnancy well and prosthetic valve on anticoagulant was not a risk factor, as seen in some studies. [8][9][10] There was no maternal mortality in our study population whereas other studies have reported maternal mortality in heart disease in pregnancy. NYHA functional class and CARPREG Risk score were validated in our study as predictors for adverse maternal outcome Our study had more adverse maternal outcome than CARPREG study, having incidence of adverse maternal outcome as 21.4%, 46.1% and 100% (Table 1) as compared to 1%, 27% and 75% found by Siu et al, in score 0, 1 or ≥2 respectively.…”
Section: Risk Factors For Adverse Maternal Outcomecontrasting
confidence: 51%
“…Prosthetic valve patients tolerated pregnancy well and prosthetic valve on anticoagulant was not a risk factor, as seen in some studies. [8][9][10] There was no maternal mortality in our study population whereas other studies have reported maternal mortality in heart disease in pregnancy. NYHA functional class and CARPREG Risk score were validated in our study as predictors for adverse maternal outcome Our study had more adverse maternal outcome than CARPREG study, having incidence of adverse maternal outcome as 21.4%, 46.1% and 100% (Table 1) as compared to 1%, 27% and 75% found by Siu et al, in score 0, 1 or ≥2 respectively.…”
Section: Risk Factors For Adverse Maternal Outcomecontrasting
confidence: 51%
“…15 Mitral regurgitation was the second commonest lesion similar to other studies. 3,16 It is well tolerated during pregnancy and mild regurgitation poses a low risk of complications. 17 A recent Brazilian study however reported that cardiac adaptations in women with mitral regurgitation are dissimilar from normal women and optimal cardiac remodeling does not occur in these patients.…”
mentioning
confidence: 99%
“…23 In an African study, pulmonary edema was present at admission in 36 out of 50 patients and there were 17 maternal deaths. 16 Cesarean section was performed for obstetric indication in 20.6% patients. In contrast, a similar study in South Africa reported 16.66% elective cesarean sections for severe heart disease.…”
mentioning
confidence: 99%
“…Data from Ethiopia show higher mortality in women, with female deaths accounting for 57.4% of the 115 cases studied 27. Diao et al 14 recently reported 17 maternal deaths in a series of 46 women (34%) from Cameroon with rheumatic heart valve disease, of which 32 had mitral stenosis. Maternal death was associated with mitral stenosis, severe tricuspid regurgitation and New York Heart Association functional class III/IV.…”
Section: Propensity To Heart Diseasementioning
confidence: 99%
“…Even when surgery is available, the choice between repair or replacement can be difficult. In a small series from Cameroon, women with prior surgical valve replacement had a better prognosis 14. However, mitral repair and aortic valve replacement with pulmonary autograft (Ross procedure) are the preferred procedures to manage left heart valve disease in young girls because they allow continued growth of the aortic valve and avoid long-term anticoagulation.…”
Section: Propensity To Heart Diseasementioning
confidence: 99%